2023
DOI: 10.18240/ijo.2023.01.19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of retinal amyloid angiopathy with transthyretin Gly83Arg variant

Abstract: AIM: To report on the clinical features of patients with retinal amyloid angiopathy (RAA) who were identified to be caused by the transthyretin (TTR) Gly83Arg variant. METHODS: Case series of five patients diagnosed with RAA was collected at Affiliated Hospital of Zunyi Medical University from January 2010 to December 2021. The clinical features, therapeutic strategies, and prognoses of all patients were reviewed. RESULTS: Five patients with a mean age of 52.00±7.23y were diagnosed as RAA. These patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In our study, perimetry revealed scotomata in corrected probabilites model corresponding to the hyporeflective lesions on enface images. FFA and indocyanine green angiography (ICGA) can provide evidence of retinal vasculopathy in the affected eye [28][29] , but most patients appear normal so that FFA and ICGA are often used to exclude other diseases. In our cases, no abnormal fluorescence was observed.…”
Section: Acute Macular Neuroretinopathy Following Sars-cov-2 Infectionmentioning
confidence: 99%
“…In our study, perimetry revealed scotomata in corrected probabilites model corresponding to the hyporeflective lesions on enface images. FFA and indocyanine green angiography (ICGA) can provide evidence of retinal vasculopathy in the affected eye [28][29] , but most patients appear normal so that FFA and ICGA are often used to exclude other diseases. In our cases, no abnormal fluorescence was observed.…”
Section: Acute Macular Neuroretinopathy Following Sars-cov-2 Infectionmentioning
confidence: 99%
“…Amyloid can build up under the superficial mucosa or in the vasculature of the urinary tract, potentially causing massive bleeding [42]. Cases of retinal haemorrhage also have been reported in patients with ATTR amyloidosis due to vascular endothelial cell damage [43,44].…”
Section: Spontaneous Bleeding Manifestations: Case Reportsmentioning
confidence: 99%